2d slab models of nanotubes based on tetragonal tio2 structures: Validation over a diameter range - Lisovski, Oleg; Piskunov, Sergei; Bocharov, Dmitry; Kenmoe, Stephane (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
One-dimensional nanomaterials receive much attention thanks to their advantageous properties compared to simple, bulk materials. A particular application of 1D nanomaterials is pho-tocatalytic hydrogen generation from water. Such materials are studied not only experimentally, but also computationally. The bottleneck in computations is insufficient computational power to access realistic systems, especially with water or another adsorbed species, using computationally expensive methods, such as ab initio MD. Still, such calculations are necessary for an in-depth understanding of many processes, while the available approximations and simplifications are either not precise or system-dependent. Two-dimensional models as an approximation for TiO2 nanotubes with (101) and (001) structures were proposed by our group for the first time in Comput. Condens. Matter journal in 2018. They were developed at the inexpensive DFT theory level. The principle was to adopt lattice constants from an NT with a specific diameter and keep them fixed in the 2D model optimization, with geometry modifications for one of the models. Our previous work was limited to studying one configuration of a nanotube per 2D model. In this article one of the models was chosen and tested for four different configurations of TiO2 nanotubes: (101) (n,0), (101) (0,n), (001) (n,0), and (001) (0,n). All of them are 6-layered and have rectangular unit cells of tetragonal anatase form. Results of the current study show that the proposed 2D model is indeed universally applicable for different nanotube configurations so that it can be useful in facilitating computationally costly calculations of large systems with adsorbates. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Published under the CC BY 4.0 license.
This research was funded by the M-ERA.NET project ?Multiscale computer modelling, synthesis and rational design of photo(electro)catalysts for efficient visible-light-driven seawater splitting? (CatWatSplit). Institute of Solid State Physics, University of Latvia as the Center of Excel-lence has received funding from the European Union?s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; DFT; Nanotubes; Slab model; TiO2; Water adsorption; Water splitting